Analysis Of Purchasing Decisions In Terms Of Product Quality, Price, And Brand Ambassador In E-Commerce - Rebekah, Felicia; Suharyanto, Suharyanto; Mildawani, M. M. Tri Susetyaning (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This study aimed to examine the elements that affect Scarlett Whitening customers' e-commerce purchase decisions. The factors studied are product quality, price, and brand ambassador. The critical data used in this study were collected directly from respondents by sending research questionnaires to Scarlett Whitening customers shopping online in Jabodetabek. In contrast, secondary data in this study came from other statistical data and websites. Non-probability purposive sampling was used to acquire the data, and there were 110 respondents. With the aid of SPSS software version 25, this kind of research uses an associative analysis method with a quantitative approach. This study discovered that Scarlett Whitening's consumer purchase decisions in e-commerce are positively and significantly impacted by product quality, price, and brand ambassador.